Romania : Forest Sector Rapid Assessment - World Bank (Washington, DC, 2014)
Romania relies on the European Structural and Investment Funds (ESIF) to achieve its commitments to the European Union (EU) 2020 targets. The use of the European Agriculture and Rural Development Fund (EARDF) requires that at least 30 percent of the budget allocated for rural development as part of the National Rural Development Plan (NRDP) be spent on the environment and addressing climate change. The forest sector rapid assessment reviews key issues in the forest sector to determine how the sector can contribute to mitigating and adapting to climate change. The assessment reviews the sector ministries measures for the 2014-2020 structural operational programs (SOPs) and NRDP to determine whether they are climate positive. The latter is an important condition for using EU structural cohesion funds (SCF) for 2014-2020. The assessment identifies operational programs and sector plans that can support the climate change objectives and fulfill the EU ex ante conditionalities for the SCF (2014-2020). The assessment also provides a basis for refining the measures in order to respond to the climate change requirement. The reimbursable advisory service phase will involve more in-depth work on the sector, offering more specific recommendations.